Improving the Vocabulary Mastery in ELT Context: Mapping Words Technique for Vocational Students - Sitti Aisyah; Novalia Tanasy (Utamax : Journal of Ultimate Research and Trends in Education, 2019)
This modern era, people are demanded to have more than one language especially English as an international language. In educational context, developing the students' ability to master English, it cannot be separated from vocabulary mastery because it can be a measurement of students, understanding of English. This research is conducted to determine the implementation of mapping words technique effectiveness in improving the student's vocabulary mastery at the third Year Students of SMK Darussalam Makassar. This quasi-experimental research used two group designs named pre-test and post-test. 60 out of 287 students as being registered as a sample. The experimental group consists of 32 students, and the control group consists of 28 students. This research applied the Mapping Words technique as the medium while the other class using the conventional method. The result of this research showed that the use of the Mapping Words technique effectively improves the students’ vocabulary, it was shown from the result of pre-test and post-test in both groups. The mean scores and standard deviation of the experimental class showed improvement where the two mean scores' deviation was/. The value of the t-test was 4.37, while the value of the t-table was 2.021 on the level of significant 0.05 (95%) and 2.704 on the level significant 0.01 (99%). This figure indicated that the value of t-calculated was higher than the t-value of t-table 4.37 > 2.021 and 2.704.